INVESTIGATION OF STRUCTURAL PROPERTIES OF PLASMA-DUST FORMATIONS IN CAPACITIVE RADIO FREQUENCY DISCHARGE - Jumabekov, A. N. (Recent Contributions to Physics, 2009)
In present paper structural properties of dust component in complex plasma in radio frequency glow discharge were studied. The possibility of investigation of «crystal-liquid» phase transition in dust structureon the basis of analysis of pair correlation distribution functions and spectra of spatial density of dust particles is shown.